ANALISIS RESPONSIVITAS BURSA SYARIAH OLEH VARIABEL MAKRO EKONOMI - Pratama, Yoghy Citra (Program Studi Pendidikan Manajemen Perkantoran, 2012)
The objectives of this study are to analyze the stock response because of M2, exchange rate Rupiah toDollar and Rate of SBI. The data used in this study are monthly time series data from January 2006 –May 2012. Those data are JII, M2, exchange rate Rupiah to Dollar and Rate of SBI. Research methodused in this study is Vector Error Correction Model (VECM). The cointegration test indicates thatamong research variables there is long term equilibrium and simultaneous relationship. The Empiricalresult of Impulse Response show that the effect of SBI discount rate and M2 is negative and the effectof exchange rate is positive. The result on variance decomposition test, show that the most effect of JIIshock is influenced by JII itself.